Potential of Saccharine Substrates for Ethanol Production - Santos, Maria do Socorro Mascarenhas; Cardoso, Claudia Andrea Lima; Silva, Emília Maria; Batistote, Margareth (Orbital: The Electronic Journal of Chemistry, 2018)
Brazil, which has a great territorial extension, with fertile soils and availability of water and, in this way, can produce a diversity of vegetal products with bioenergetics potential. Thus, this study aims to evaluate the technological characteristics of saccharine substrates of direct fermentation for ethanol production as well as to analyze the fermentative profile of FT-858 yeast in different culture conditions. For this, a bibliographic survey was carried out comparing the technological qualities of the analyzed biomasses. To evaluate the fermentative capacity, the saccharine substrates were used at concentrations of 18 and 32°Brix at 30 °C for 24 hours in test tubes containing Durhan tubes. For the analysis of the fermentation profile the yeasts were grown in 2% YPD medium and the biomass obtained was used in the saccharine substrates of direct fermentation for 50 hours. The saccharine substrates presented potential for ethanol production: sugar cane and saccharine sorghum. The yeast FT-858 presented fermentation capacity in the different substrates in the concentrations of Brix analyzed, presenting a better fermentative performance in sugarcane broth and the highest concentrations of ethanol occurring in the times of 10 and 15 hours of fermentation for both substrates. DOI: http://dx.doi.org/10.17807/orbital.v10i1.1013